2000
DOI: 10.1016/s0014-5793(00)01266-7
|View full text |Cite
|
Sign up to set email alerts
|

Opposite role of changes in mitochondrial membrane potential in different apoptotic processes

Abstract: We have studied the role of changes in mitochondrial membrane potential (v v8 8) in two widely-used models of apoptosis, such as dexamethasone-treated rat thymocytes and U937 human cells treated with tumor necrosis factor-K K and cycloheximide. To dissipate v v8 8, we used low concentrations of valinomycin, unable per se to induce apoptosis, and demonstrated that the decline in v v8 8 exerts opposite effects in the two models. Indeed, in U937 cells, depolarization of mitochondria increased apoptosis, which dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Our preliminary studies indicate that both apoptotic stimuli induce a much deeper decrease in ATP levels in U937 V cells when compared to the reference cells. Additionally, a rapid decrease in MMP might suggest that ATP is depleted and the process of apoptosis might be inhibited [24,26]. Although an MMP decrease can be a consequence of the presence of reactive oxygen species (ROS) [8], in our study the generation of ROS observed in the U937 V cells seemed to be rather the consequence of a decrease in the MMP, similarly to that reported by other authors [9,27,28].…”
Section: Discussionsupporting
confidence: 88%
“…Our preliminary studies indicate that both apoptotic stimuli induce a much deeper decrease in ATP levels in U937 V cells when compared to the reference cells. Additionally, a rapid decrease in MMP might suggest that ATP is depleted and the process of apoptosis might be inhibited [24,26]. Although an MMP decrease can be a consequence of the presence of reactive oxygen species (ROS) [8], in our study the generation of ROS observed in the U937 V cells seemed to be rather the consequence of a decrease in the MMP, similarly to that reported by other authors [9,27,28].…”
Section: Discussionsupporting
confidence: 88%
“…In the latter, decreases in Dw m and thus a reduction in ATP for protein synthesis inhibited or delayed apoptosis until such time that reduced ATP levels were the cause of cellular demise (Salvioli et al 2000). Human osteosarcoma cells were observed to undergo mitochondrial permeability transition and mitochondrial swelling in a reversible manner and with the marked absence of apoptosis (Minamikawa et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have however cast doubt on the involvement of mitochondria on regulating apoptosis reporting that cytochrome c release is not necessary for cell death and that its release is not always facilitated by mitochondrial membrane depolarisation (Hatano et al 2000). Further still, there are suggestion that mitochondrial membrane depolarisation is in itself capable of inducing caspase activation and thus apoptosis (Salvioli et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…on induction of MPT (Pastorino et al, 1998). Some questions have been raised about the involvement of mitochondrial ÁÉ collapse and cytochrome c release as markers for apoptosis, since they are cell type-and inducer-dependent phenomena (Tang et al, 1998;Salvioli et al, 2000). However, several studies point out that mitochondria play a key role in apoptotic cascade and that the induction of MPT leads to cell death by releasing several activators of apoptosis (Fadeel et al, 1999;Tafani et al, 2000).…”
Section: Discussionmentioning
confidence: 99%